Translabyrinthine Petrous Apex Cholesteatoma Surgery with Hearing Preservation - Sudhoff, Holger; Klingebiel, Randolf; Scholtz, Lars-Uwe; Todt, Ingo (Case Reports in Otolaryngology, 2021)
Objective. To introduce a novel surgical approach to petrous apex lesion (PA) with superior semicircular canal plugging for hearing preservation. Patient. A 63-year-old patient presented with a recurrent cholesteatoma of the left petrous apex. The patient had a long-term history of cholesteatoma and MRI with diffusion-weighted imaging (DWI) detected a suspicious lesion in the left petrous apex on follow-up. Intervention. The cholesteatoma could be completely removed from the petrous apex with partial superior semicircular canal plugging and removal with hearing preservation. Outcomes. Cholesteatomas of the temporal bone are managed by surgery with complete excision of the lesion. Results. The translabyrinthine approach, generally useful in nonhearing ears, could be utilized with the additional technique of superior semicircular canal plugging to preserve hearing in this patient. Conclusions. This case highlights the possibility of a hearing preservation strategy for PA cholesteatomas using a translabyrithine approach.